Development of IRME based mathematics learning videos integrated local cultural context to enhance sixth grade elementary students’ understanding of mixed arithmetic operations - Solina, Eva; Somakim; Wargadalem, Farida R; Raharjo, Makmum (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aims to develop a mathematics learning video based on the Indonesian Realistic Mathematics Education (IRME) approach by integrating the local cultural context of Jumputan Gambo fabric to support sixth-grade elementary students’ understanding of mixed arithmetic operations. Method: This research employed a development research design using the Rowntree model, which consists of planning, development, and evaluation stages. The evaluation stage was conducted using Tessmer’s formative evaluation framework, including self-evaluation, expert review, one-to-one evaluation, small group evaluation, and field testing. Four expert validators assessed the developed learning video in terms of media design, content accuracy, language clarity, and instructional design. Practicality data were obtained through student response questionnaires, while effectiveness was measured using pretest and posttest assessments. The collected data were analyzed using descriptive statistics and normalized gain (N-Gain). Findings: The results indicate that the developed learning video met the criteria of validity, practicality, and effectiveness. Expert validation showed a very valid category with an average score of 92.85%. Practicality results from the one-to-one and small group trials ranged from 92.22% to 100%. The effectiveness test demonstrated an improvement in students’ learning outcomes, with the average score increasing from 56.77 on the pretest to 85.48 on the posttest. The N-Gain value of 0.70 indicates a high level of learning improvement. Significance: The study demonstrates that integrating IRME principles with culturally contextualized video learning supports meaningful mathematics learning and provides practical guidance for teachers in designing contextual mathematics instruction aligned with the Merdeka Curriculum.